2019
DOI: 10.3390/ani9100725
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Forage Proportion on Feed Intake, Growth Performance, Nutrient Digestibility, and Enteric Methane Emissions of Holstein Heifers at Various Growth Stages

Abstract: Simple SummaryEnteric methane (CH4) emission from ruminants is a large source of anthropogenic greenhouse gas production, which is an inevitable by-product when feedstuff is digested and fermented in the rumen, representing approximately 7% of dietary energy loss. Although the Chinese government has committed to reduce CH4 emissions under the requirement of the Copenhagen Accord (2009), there is lack of accurate CH4 emission data from young cows as the guideline of IPCC gives little consideration to the variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 39 publications
3
15
0
2
Order By: Relevance
“…Jiao et al [ 51 ] also observed that increasing the level of supplementation (2.0, 4.0, 6.0, and 8.0 kg/cow/day) in dairy cows grazing perennial ryegrass led to increased milk production per cow per day, thereby reducing CH 4 emissions per unit of produced milk due to the increase in soluble carbohydrates. As has been shown, an increased proportion of cereal concentrates in the diet decreases enteric CH 4 emissions, whereas the intake of non-structural carbohydrates such as starch increases hydrogen and CH 4 production in the rumen [ 52 ]. Accordingly, Zhu et al [ 48 ] suggested that one option to mitigate CH 4 emissions in dairy cows is to increase milk production through optimization of the ingredients in the diet.…”
Section: Discussionmentioning
confidence: 99%
“…Jiao et al [ 51 ] also observed that increasing the level of supplementation (2.0, 4.0, 6.0, and 8.0 kg/cow/day) in dairy cows grazing perennial ryegrass led to increased milk production per cow per day, thereby reducing CH 4 emissions per unit of produced milk due to the increase in soluble carbohydrates. As has been shown, an increased proportion of cereal concentrates in the diet decreases enteric CH 4 emissions, whereas the intake of non-structural carbohydrates such as starch increases hydrogen and CH 4 production in the rumen [ 52 ]. Accordingly, Zhu et al [ 48 ] suggested that one option to mitigate CH 4 emissions in dairy cows is to increase milk production through optimization of the ingredients in the diet.…”
Section: Discussionmentioning
confidence: 99%
“…Estimated enteric CH 4 emission is the by-product of ruminal fermentation via methanogenesis and is thus substantially affected by a range of factors, including dietary components [ 65 ]. Thus, the methane production variation in our study among the dietary treatments might be related to the difference in the proportion of nutrients, such as the high NDF content of the NPH-based TMR [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the methane production variation in our study among the dietary treatments might be related to the difference in the proportion of nutrients, such as the high NDF content of the NPH-based TMR [ 11 ]. Specifically, the fermentation of fibrous materials favors the formation of acetate and butyrate which contribute to the production of CH 4 [ 65 ]. In our study, methane emission per kg of OM intake was lower for the TTS, NGH, and BhH diets than for NPH, thereby indicating that highly digestible roughages are promising means for reducing CH 4 emission.…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to the polyphenolic compounds in legumes, such as condensed tannins, which have been previously shown to be negatively correlated with CH 4 emissions [33]. For rumen fermentation, there is a negative relationship between CH 4 emissions and propionate formation in the rumen, which could depress the activity of methanogens [4,5]. In this study, the lower ratios of acetate to propionate (Table 5) correspond to lower CH 4 emissions after forage supply (Figure 2d) in diet groups with a higher proportion of legumes and this is consistent with the above finding.…”
Section: Discussionmentioning
confidence: 99%
“…A low NUE could contribute more ammonia emissions to the air and more manure N outputs to the soil [2], which could damage air quality [3] and lead to soil nitrification and acidification [2]. The enteric CH 4 emissions from ruminants not only represent a loss of diet energy [4] but could also contribute to global warming [5]. The development of a diet that can improve the NUE and reduce enteric CH 4 emissions is in demand and would be beneficial to both animal husbandry and in facing global environmental challenges [6,7].…”
Section: Introductionmentioning
confidence: 99%